(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Rubber and rubber-metal (RM) elements are successfully used as bearing, joints, compensating devices, vibration and shock absorbers in civil engineering and machine building because of rubber and rubberlike materials (elastomers) have a capability of absorbing input energy much better than other construction materials. The elastic properties of rubber in such supports allows reverse backward to its original position under dynamic load action. Along with the instantaneous elastic deformation these materials exhibit a retarded elastic deformation, viscous flow (creep) and relaxation.The mechanical properties of rubber which are necessary for the optimal design of antivibration devices are next: bulk modulus of compression, dynamic and static shear modulus, energy dissipation factor. To describe the relationship between the compressive (or shear) stress σ(t) and strain ԑ(t) the creep and relaxation kernel, taking into account the viscoelastic properties of the rubber, is used. The kernels proposed by A. Rzhanitsin, Y. Rabotnov, M. Koltunov give satisfactory results for the mechanical properties of rubber in the mean frequency domain (10-3 < ω < 103 s-1). In this paper for the accounting of dissipative properties of the rubber Rabotnov’s kernel is used, the energy loss during one oscillation period is calculated. The flat-type RM absorber with kinematic excitation, which lower base oscillates harmonically is considered, oscillation parameters of the upper base on which the protected object is placed, are calculated. Damping properties are expressed by the ratio of the amplitude of the forced oscillations of the upper base (and object) to the amplitude of driving lower base.